Clinical Application of Indocyanine Green Fluorescence Imaging in the Resection of Hepatoblastoma: A Single Institution's Experiences - Shen, Yuanchao; Zheng, Manna; Li, Jiahao; Tan, Tianbao; Yang, Jiliang; Pan, Jing; Hu, Chao; Zou, Yan; Yang, Tianyou (Frontiers in Surgery, 2022)
Purpose Indocyanine green (ICG) fluorescence imaging is becoming increasingly popular in adult oncologic surgery, but remains relatively uncommon in pediatric oncologic surgery. Herein, we report our experience with the use of ICG fluorescence imaging in the resection of hepatoblastoma (HB). Patients and Methods Hepatoblastoma patients who underwent liver resection with ICG fluorescence imaging between January 2020 and March 2021 were included in this study. Patients’ demographic data, clinical information, and detailed information of the use of ICG fluorescence imaging were retrospectively reviewed. Results Sixteen HB patients underwent ICG fluorescence imaging-guided liver resection. There were 11 males and 5 females, age ranged from 8 to 134 months. The initial alpha-fetoprotein ranged from 436 to 528,390 ng/ml. There were one pre-treatment extent of tumor stage I, nine stage II, four stage III, and two stage IV. Three patients underwent up-front hepatectomy, 13 patients received 2–8 cycles of platinum-based neoadjuvant chemotherapy and underwent delayed hepatectomy. ICG (0.5 mg/kg) was given intravenously 48–72 h prior to surgery. The operative time ranged from 180 to 400 min. All patients achieved negative surgical margins. In two patients, ICG identify additional lesions which were not detected in preoperative imaging. Conclusion ICG fluorescence imaging is useful in the resection of HB and may detect small lesions not shown in preoperative imaging.